2018
DOI: 10.1371/journal.pone.0197264
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal gait pattern emerges during curved trajectories in high-functioning Parkinsonian patients walking in line at normal speed

Abstract: BackgroundSeveral patients with Parkinson´s disease (PD) can walk normally along straight trajectories, and impairment in their stride length and cadence may not be easily discernible. Do obvious abnormalities occur in these high-functioning patients when more challenging trajectories are travelled, such as circular paths, which normally implicate a graded modulation in the duration of the interlimb gait cycle phases?MethodsWe compared a cohort of well-treated mildly to moderately affected PD patients to a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 145 publications
(180 reference statements)
3
24
0
Order By: Relevance
“…Finally, the double support time variable is represented in the pace/rhythm factor. This variable is reported to be increased in patients with PD, not only in linear walking [34], but also in curved trajectories [45]. Double support time is a phase of gait cycle considered to be a stabilizing component of gait [46]: not unexpectedly, fallers usually have an increased double support time.…”
Section: Pace/rhythm Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the double support time variable is represented in the pace/rhythm factor. This variable is reported to be increased in patients with PD, not only in linear walking [34], but also in curved trajectories [45]. Double support time is a phase of gait cycle considered to be a stabilizing component of gait [46]: not unexpectedly, fallers usually have an increased double support time.…”
Section: Pace/rhythm Factormentioning
confidence: 99%
“…The variability factor refers to unsteadiness and arrhythmic pattern of stepping [47]. The increased gait variability and impaired rhythmicity in PD worsen as the PD progresses [45,48,49] and may reflect reduced automaticity and damaged locomotor synergies [50,51]. Increased gait variability is usually associated with an increased fall risk in both elderly individuals [52] and patients with PD [53], suggesting that increased variability may be a very useful element in fall risk assessment.…”
Section: Variability Factormentioning
confidence: 99%
See 1 more Smart Citation
“…If these adaptations can be considered trivial for healthy people, they represent an actual challenge for the elderly [ 1 , 6 , 7 ] and for patients with neurological disorders [ 8 , 9 , 10 , 11 ]. Furthermore, even if it is not clear if falls are more frequent during turns, it has been shown that falling during a turn has an increased risk of serious injury [ 12 ], and that staggering when turning is a prominent characteristic of recurrent fallers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether IMU-based GE detection is still valid in more complex walking tasks is yet to be shown. Daily-life gait is likely influenced by obstacle negotiation (approximately 30% of daily-life gait is spent along curved trajectories [22]) and dual-/multi-tasking [5].…”
Section: Introductionmentioning
confidence: 99%